Pd–Tetrahydrosalan‐Type Complexes as Catalysts for Sonogashira Couplings in Water: Efficient Greening of the Procedure. Issue 8 (3rd July 2014) - Voronova, Krisztina; Homolya, Levente; Udvardy, Antal; Bényei, Attila C.; Joó, Ferenc
Abstract New sulfonated tetrahydrosalen‐type ligands and their water‐soluble palladium(II) complexes have been synthesized. The palladium(II) complexes catalyze the Sonogashira coupling (23 examples) of various aryl halides (including chloroarenes) with terminal alkynes, with good to excellent conversions under mild conditions (80 °C, air, no CuI cocatalyst) in aqueous–organic mixtures and turnover frequencies of up to 2790 h−1. Under optimized reaction conditions to minimize environmental contamination, diphenylacetylenes can be isolated in 76–98 % yield. The aqueous catalyst solution can be recycled four times with decreasing activity; however, yields between 93 and 98 % can still be achieved with extended reaction times. Several water‐insoluble products can be isolated in excellent yield by simple filtration and purification by washing with water; this method is used, for the first time, for this type of CC coupling procedure.